APLICACIÓN DE CÓMPUTO MÓVILY PERVASIVO PARA EL MONITOREO NO INVASIVO DE LA DIABETES EN TIEMPO REAL - Colmenares-Guillen, Luis Enrique; Ruiz, Maya Carrillo; Niño, Edilberto Huerta (European Scientific Journal, ESJ, 2015)
Given the alarming increase of people with diabetes in the world, they are looking for different alternatives, using as many available technological resources and thus have an efficient monitoring of this noncommunicable disease (NCD). This paper presents a viable alternative, to have an efficient and non-invasive monitoring, using free software and hardware, such as, Android and Arduino. As well as various non-invasive, such as GSR (Galvanic Skin Response), to measure glucose levels, accelerometers to determine the location of the person body, PulseOximeters, to determine each patient’s pulse and GPS sensors, is a Global Positioning System, it helps to have the geographic position of the person. Each of these sensors interact with the system in general, with the purpose of create a pervasive environment, where the user can have a monitoring and control of diabetes and pulse additionally its position and geographical location.